2011
DOI: 10.1021/ma102451b
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Bulk Structural Characterization of a High-Mobility Electron-Transporting Polymer

Abstract: This publication investigates the microstructure of the high electron mobility polymer poly([N,N 0 -bis(2-octyldodecyl)-11 naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5 0 -(2,2 0 -12 biothiopene)) (P(NDI2OD-T2)) using a combination of grazing incidence X-ray diffraction (GIXD), near-edge X-ray absorption fine structure (NEXAFS), and optical spectroscopies. GIXD measurements confirm extended in-plane lamellae ordering and out-of-plane π-π stacking. Angle-resolved surface-sensitive NEXAFS measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
169
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(214 citation statements)
references
References 37 publications
43
169
1
Order By: Relevance
“…[13][14][15] Vertical charge transport measurements showed a signifi cant drop of the electron mobility upon meltannealing, in accordance with the observed texture changes, where a higher mobility was seen for the face-on orientation, suggestive of effi cient charge transport along the π-stacking direction. On the other hand, transistor performance appeared to be less affected by the structural changes.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…[13][14][15] Vertical charge transport measurements showed a signifi cant drop of the electron mobility upon meltannealing, in accordance with the observed texture changes, where a higher mobility was seen for the face-on orientation, suggestive of effi cient charge transport along the π-stacking direction. On the other hand, transistor performance appeared to be less affected by the structural changes.…”
Section: Introductionsupporting
confidence: 77%
“…While at fi rst it was assumed that P(NDI2OD-T2) forms mainly amorphous layers, [ 6 ] X-ray diffraction analysis and transmission electron microscopy (TEM) revealed the semicrystalline character of P(NDI2OD-T2) thin fi lms in recent years. [13][14][15][16][17] Rivnay et al were the fi rst to show a remarkable degree of in-plane order in as-cast fi lms with an unconventional face-on texture in the bulk. [ 13 ] A striking texture change was observed upon melt-annealing, when the polymer chains undergo a transition from mainly face-on to edge-on.…”
mentioning
confidence: 99%
“…[13] Furthermore, recent studies addressed detail of P(NDI2OD-T2) film microstructure, how it can be varied with thermal annealing, and how this affects FET performance. [14] However, fundamental questions remain about the nature of P(NDI2OD-T2) film microstructure in the very first few layers of the transistor channel.…”
Section: Doi: 101002/adma201103800mentioning
confidence: 99%
“…This is also corroborated by recent observations on the texture of P(NDI2OD-T2) thin films after melt annealing, revealing an increased crystallinity along with edgeon lamellar conformation upon energy minimization. [14] In general, the molecular orientation with respect to the substrate in the mono-/multilayer films critically depends on the relative strengths of the molecule-substrate versus intermolecular interactions. In the present case, the out-of-plane molecular order is reached at the air/water interface during compression and thereby transferred to the substrate.…”
Section: Doi: 101002/adma201103800mentioning
confidence: 99%
“…This particular morphology allows good electron transport in both organic diodes and field-effect transistors (OFETs), with high in-plane mobilities of ∼0.1-0.6 cm 2 ·V -1 ·s -1 even in the presence of a substantial degree of disorder (11). However, film morphologies with predominantly edge-on oriented polymer chains were observed to yield lower performance in both diodes and top-gated OFETs because of the reduced out-of-plane mobility and larger injection barrier (16)(17)(18)(19). In a recent publication, Neher and coworkers also showed that this polymer has a strong tendency to aggregate, which greatly affects the bulk optical and electrical properties (20,21).…”
mentioning
confidence: 99%